2016
DOI: 10.1103/physrevb.93.205121
|View full text |Cite
|
Sign up to set email alerts
|

Energy transport between two integrable spin chains

Abstract: We study the energy transport in a system of two half-infinite XXZ chains initially kept separated at different temperatures, and later connected and let free to evolve unitarily. By changing independently the parameters of the two halves, we highlight, through bosonisation and time-dependent matrix-product-state simulations, the different contributions of low-lying bosonic modes and of fermionic quasi-particles to the energy transport. In the simulations we also observe that the energy current reaches a finit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 67 publications
7
84
0
Order By: Relevance
“…Similar results were obtained in the framework of conformal field theory and Luttinger liquid descriptions [25][26][27][28][29][30][31][32][33][34][35][36][37]. In the presence of interactions the situation was less clear [38][39][40][41][42][43][44][45][46][47], but, eventually, Refs [48,49] have shown that the continuity equations satisfied by the (quasi)local conserved quantities are sufficient to characterize the late-time behavior. The framework developed in Refs [48,49] is now known as generalized hydrodynamics [48], where "generalized" is used to emphasize that integrable models have infinitely many (quasi)local charges [50].…”
supporting
confidence: 65%
“…Similar results were obtained in the framework of conformal field theory and Luttinger liquid descriptions [25][26][27][28][29][30][31][32][33][34][35][36][37]. In the presence of interactions the situation was less clear [38][39][40][41][42][43][44][45][46][47], but, eventually, Refs [48,49] have shown that the continuity equations satisfied by the (quasi)local conserved quantities are sufficient to characterize the late-time behavior. The framework developed in Refs [48,49] is now known as generalized hydrodynamics [48], where "generalized" is used to emphasize that integrable models have infinitely many (quasi)local charges [50].…”
supporting
confidence: 65%
“…Groundbreaking cold-atom experiments have also investigated several aspects of the coherent dynamics of closed quantum many-body systems [16][17][18][19][20][21][22][23][24]. These research efforts allowed to faithfully address how the presence of impurities and inhomogeneities may affect the quantum transport phenomena, also far from the linearresponse regime [25][26][27][28][29].As a paradigmatic example, we study a setup composed of two different semi-infinite spin-1/2 chains connected through a junction at x = 0 (see Fig. 1) [27].…”
mentioning
confidence: 99%
“…These research efforts allowed to faithfully address how the presence of impurities and inhomogeneities may affect the quantum transport phenomena, also far from the linearresponse regime [25][26][27][28][29].As a paradigmatic example, we study a setup composed of two different semi-infinite spin-1/2 chains connected through a junction at x = 0 (see Fig. 1) [27]. In order to highlight the resistive effects taking place at the junction, we consider two models for which ballistic transport of spin and energy has been unambiguously demonstrated.…”
mentioning
confidence: 99%
“…Inhomogeneous quenches, in general, pose a more difficult problem than homogeneous ones with fewer exact or approximate results [28][29][30][31][32][33][34][35][36]. One promising approach exploits hydrodynamical description assuming the separation of spatial and temporal scales and a local (GGE) equilibrium, and is supported both by numerical simulations and experimental observations [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%